Between Two Pasts: Dictatorships and the Politics of Memory in Bolivia. (May 2015) - García Jerez, Francisco Adolfo; Müller, Juliane
The presence of Evo Morales in the government of Bolivia raised expectations of change with regard to the politics of memory, justice, and the social and economic compensation for victims of the country's dictatorships between 1964 and 1982. However, according to human rights organizations, these expectations have been only partly fulfilled. This can be explained by three fundamental factors: the government's pursuit of an alliance with the military in order to accomplish its project, the collapse of the parties and traditional organizations of the left, and the articulation of a new narrative to consolidate the government's project in terms of indigenous and anti-neoliberal nationalism. The latter two factors have resulted in the systematic political use of long memory (anticolonial resistance) and short memory (the popular protests of the 1990s and 2000s) and the partial displacement of an intermediate memory (the 1952 Revolution) and the memory of the dictatorships. La presencia de Evo Morales en el gobierno de Bolivia generó expectativas de cambio con respecto a la política sobre la memoria, la justicia y la compensación social y económica para las víctimas de las dictaduras del país entre 1964 y 1982. Sin embargo, de acuerdo con las organizaciones de derechos humanos, estas expectativas sólo se han cumplido de forma parcial. Esto puede explicarse a través de tres factores fundamentales: la búsqueda de una alianza con los militares por parte del gobierno para poder llevar a cabo su proyecto, el colapso de los partidos y organizaciones tradicionales de izquierda, y la articulación de una nueva narrativa para consolidar el proyecto del gobierno en términos de un nacionalismo indígena y la oposición al neoliberalismo. Los últimos dos factores han resultado en un uso sistemático de la memoria larga (la resistencia anticolonial) y la corta (las protestas populares de los años noventa y el 2000), así como la dislocación parcial de una memoria intermedia (la Revolución de 1952) y la memoria de las dictaduras.